Ecofeminism in “Modern Women Bali” Magazine - Made Sani Damayanthi Muliawan; Radha Andhra Swari (Pusat riset dan Inovasi Nasional, 2025)
Ecofeminism encompasses a broader perspective, linking environmental issues with social issues. Previous research has shown that environmental discourse generated by various actors, including the government, NGOs, and the media, plays a significant role in shaping public awareness and behavior. However, the phenomenon of women often being excluded from decision-making regarding environmental policies requires special attention. In this digital era, women can share stories, adaptation strategies, and sustainable practices in addressing environmental issues through various platforms. This study aims to analyze the ideology of the women's community embodied in eco-discourse on the Modern Women Bali magazine. The research method applied is a qualitative method with data in the form of eco-discourse on the Modern Women Bali magazine. Results show that the ideologies of ecofeminism found in the media include women’s environmental care, women’s support for local sustainability, women’s role as guardian of nature, and women’s growth through nature.